The dancing palm tree and other Nigerian folktales - Walker, Barbara K. (Texas Tech University Press, 1990)
This collection of eleven tales from Nigeria includes "The Boy and the Leopard," "The King and the Ring," and "The Reward of Treachery." Also contains a glossary and explanation of customs.